Sosialisasi Dakwah Melalui Lensa Bahasa dan Budaya: Pendekatan Kultural dalam Pengembangan Pesan Islami - Aini Wahyu Ningtyas, Baqiya; Subekti; Titie Solihati, Ade; Sugianto; Sobirin (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
This Community Service Program (PKM) aims to develop da'wah methods based on local culture and language in order to convey Islamic messages effectively to the community. This activity was carried out through intensive training at the Bonavida Singgeura Milir Foundation, Indramayu, by utilizing a cultural approach as the main lens in developing Islamic messages. Through a series of presentation sessions, interactive discussions, and hands-on practice, participants were invited to understand the importance of cultural adaptation in da'wah so that Islamic values can be better received. The results of the program showed an increase in participants' understanding and skills in using local cultural elements to convey Islamic messages. Participants also appreciate cultural diversity as part of the inclusive teachings of Islam. The implementation of this PKM is expected to be an effective model in spreading Islamic values through a cultural approach, as well as strengthening the identity and harmony between religion and local culture. Key Words: community service, culture, da'wah, socialization, training, Indramayu Regency.